2016
DOI: 10.2131/jts.41.195
|View full text |Cite|
|
Sign up to set email alerts
|

Retraction: <i>In utero</i>-exposed di(<i>n</i>-butyl) phthalate induce dose dependent, age-related changes of morphology and testosterone-biosynthesis enzymes/associated proteins of Leydig cell mitochondria in rats

Abstract: -Female pregnant Sprague-Dawley rats were intragastrically (ig) administered di(n-butyl) phthalate (DBP) at four doses (0, 10, 50 and 100 mg/kg) during gestation days (GD) 12-21 (n = 5 per group). The age-related morphological changes of Leydig cell mitochondrion (LC-Mt) and testosterone biosynthesis enzymes/associated genes/proteins expression levels were investigated. As compared to the control (no DBP), the 10 mg, and 50 mg DBP dose groups, the 100 mg DBP dose group at weeks 5 and 7 showed a significant amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 35 publications
2
7
0
2
Order By: Relevance
“…The decrease of Vim in Sertoli cells seemed to be linked to testicular testosterone levels (Wakui et al, 2013;Motohashi et al, 2016). Moreover, the present study also shows that new morphometric methods can be used widely for quantitative analysis of cellular cytoplasmic filaments.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The decrease of Vim in Sertoli cells seemed to be linked to testicular testosterone levels (Wakui et al, 2013;Motohashi et al, 2016). Moreover, the present study also shows that new morphometric methods can be used widely for quantitative analysis of cellular cytoplasmic filaments.…”
Section: Discussionsupporting
confidence: 64%
“…In the present study, rats in utero were exposed to DBP (intragastrically, 100 mg/kg/day) (Wakui et al, 2013;Motohashi et al, 2016), and the perinuclear volume of Vim microfilaments in Sertoli cells was quantified at 7, 9, 14, and 17 weeks using improved electron microscopy morphometric quantitative analysis techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Histomorphological analysis of rat testes after exposure to di(n-butyl) phthalate revealed an increased Leydig cell number that showed swollen mitochondria (Ha et al 2016 ). In animals, exposed to di(n-butyl) phthalate in utero , dose-dependent and age-related changes of Leydig cell mitochondria morphology, function and associated proteins were observed (Motohashi et al 2016 ). Also, in tumors, Leydig cell organophosphate flame retardants affected mitochondrial activity, cell survival and superoxide production (Schang et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The testicular T levels via the DBP treatment group were significantly lower (p < .05) than the control group at all 4 time points (i.e., weeks 7, 9, 14, and 17; Figure 1I). We previously demonstrated that in utero DBP exposure decreased T levels by causing dysfunction of Leydig cells Wempe, Mutou, Okayama, et al 2016;. Testicular T is a determinant of spermatogenesis, which binds with the androgen-binding protein of Sertoli cells to produce glycoprotein (b globulin).…”
Section: Discussionmentioning
confidence: 99%